Unlocking the Secrets of Effective Teaching: An Exploration of Positive Emotions During Telecollaboration - Azri, Adlina Nur; Drajati, Nur Arifah (ELE Reviews: English Language Education Reviews, 2024)
In recent years, the recognition of teachers’ well-being has gained worldwide attention. Language teacher well-being has a significant contribution to classroom activity. This study explores a pre-service English teacher’s positive emotions of well-being based on PERMA and its impact on future careers. Positive emotions are the presence of positive emotions, lack of negative emotions, and life satisfaction. Telecollaboration provides a beneficial space to get the chance to expand content knowledge, increase techno-pedagogical abilities, improve the methodology of teaching, and achieve a sense of well-being. This study used autobiographical narratives to capture the researcher’s positive well-being experiences. Data were gathered through diaries and artifacts in the form of photos and screenshots during telecollaboration. The researcher used a thematic analysis technique to analyze the data. The findings underscore the presence of positive emotions that influence the outcomes of pre-service teachers, while negative emotions shift into positive feelings, thus contributing to personal development. These experiences lead the pre-service English teacher into an effective prospective educator for the future.